Animal kingdom-1 - Arma, Tom; Arma, Tom; Dreamland Publications (Dreamland Publications New Delhi, 2003)
A delightful book showcasing adorable baby animals dressed in charming costumes, captured through the lens of renowned photographer Tom Arma. This book aims to entertain and educate young readers about the animal kingdom.
Book suitable for toddlers. Features vibrant colour photographs of baby animals in various costumes. Designed to introduce young children to different animals in an engaging manner.
Keywords: Animals, Picture books for children